ChemInform Abstract: Catalytic Enantioselective Diarylation of Alkenes. Issue 20 (April 2016) - You, Wei; Brown, M. Kevin
Abstract: A protocol for preparation of highly enantioenriched 2, 3‐dihydrobenzofurans and indolines is developed.